Technology convergence and digital divides. A country-level evidence for the period 2000-2010 - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
The paper, mostly empirical in nature, investigates issues on cross-national new information and communication technologies (ICTs) adoption patterns and growth directions. In the period of 2000-2010, a great number of countries underwent substantial changes on the field of ICTs implementation. Many of them made a great “jump” starting with almost “zero level” of ICTs adoption in year 2000, and during the 10 – year period were implementing ICTs at astonishingly high pace. Despite the obvious positive impact that ICTs have on overall society and economy condition, rapid changes can also generate higher inequalities on the field. The paper focuses mainly on capturing these changes. It also aims to confirm or reject the hypothesis on growing inter-country inequalities in ICTs adoption. The target of the paper is twofold. Firstly, we explain the magnitude of past and present differences in digitalization level among countries; secondly, we concentrate digital technology convergence. We apply three approaches to convergence – beta-convergence, sigma-convergence and quantile-convergence (q-convergence), to check if relative division between countries was growing or diminishing in the time span 2000-2010. Additionally we check if countries of the given sample tend to form convergence clubs in the relevant years. The analysis is run for the sample consisted of 145 economies and the time coverage is 2000-2010. All data applied in the research are drawn from the International Telecommunication Union statistical databases.
Keywords: C22; O11; O50; O33; 330; technology; convergence; ICTs; quantile convergence; clusters; technology clubs